Kritik Komedi Berujung Bui (LEGAL DIALOGICA, 2025)
This research aims to analyze the view of positive criminal law on social criticism delivered by comics. The focus is on understanding the limits of freedom of opinion and expression and potential conflicts with the law, identifying articles in the Criminal Code that can ensnare comics when delivering critical material.The method used in this research is normative juridical, with data collection from laws and regulations, including the Criminal Code. The results show that comics face difficulties in delivering social criticism. Material that is considered insulting to individuals or institutions risks violating criminal law. Although the constitution guarantees freedom of speech, there are limits that must be observed, especially regarding sensitive issues such as politics, religion and race. This research emphasizes the importance of comics' understanding of legal boundaries and social sensitivity. Social criticism delivered through stand-up comedy must be relevant, constructive and not violate the law to prevent conflicts that can disrupt social harmony. Therefore, it is important for comics to learn legal boundaries in order to contribute positively to social discourse without facing legal risks.Abstrak:Penelitian ini bertujuan untuk menganalisis pandangan hukum pidana positif terhadap kritik sosial yang disampaikan oleh komika. Fokusnya adalah memahami batasan kebebasan berpendapat dan berekspresi serta potensi konflik dengan hukum, mengidentifikasi pasal-pasal dalam KUHP yang dapat menjerat komika saat menyampaikan materi kritis Penelitian ini menggunakan Metode yang digunakan adalah normatif yuridis, dengan pengumpulan data dari peraturan perundang-undangan, termasuk KUHP. Hasil penelitian menunjukkan bahwa komika menghadapi kesulitan dalam menyampaikan kritik sosial. Materi yang dianggap menghina individu atau institusi berisiko melanggar hukum pidana. Meskipun konstitusi menjamin kebebasan berpendapat, ada batasan yang harus diperhatikan, terutama terkait isu sensitif seperti politik, agama, dan ras. Penelitian ini menekankan pentingnya pemahaman komika terhadap batasan hukum dan sensitivitas sosial. Kritik sosial yang disampaikan melalui stand up comedy harus relevan, konstruktif, dan tidak melanggar hukum untuk mencegah konflik yang dapat mengganggu harmoni sosial. Oleh karena itu, penting bagi komika untuk mempelajari batasan hukum agar dapat berkontribusi positif terhadap diskursus sosial tanpa menghadapi risiko hukum.